Challenges and perceptions of e-learning for educational sustainability in the “new normality era” - Fülöp, Melinda Timea; Breaz, Teodora Odett; Topor, Ioan Dan; Ionescu, Constantin Aurelian; Dragolea, Larisa-Loredana (Frontiers in Psychology, 2023)
When all universities suddenly had to switch to distance learning in March 2020 due to the COVID-19 regulations, all universities were faced with the challenges of e-learning. As with all things in life, there are challenges in e-learning that you may encounter at some point. Whether you're struggling with a lack of budget or adoption. The role of digitalization is to ensure that we reach the university's long-term sustainability. The future of e-learning depends not least on future generations, which are increasingly facing the acceptance of new technologies. Therefore, this study aimed to analyse the factors that stimulus the acceptance of technology by students in universities. The novelty of the study is the choice of a developing country. The results indicate that external factors do not influence perceived usefulness. Respectively, students consider that the perceived ease of use does not influence the behaviour intention to use new technologies. Finally, we present the research's conclusions, limits, and perspectives on the acceptance of technologies to ensure sustainability in universities.